2022
DOI: 10.1002/edm2.377
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat loss by whole‐body electromyostimulation is attenuated in male and absent in female older Non‐Insulin‐Dependent diabetes patients

Abstract: Introduction: Type 2 diabetes and its reversal correlate with increases and decreases in visceral fat (VF). Resistance exercise reduces VF in healthy persons, but little is known in type 2 diabetes. Muscle contractions induced by whole-body electromyostimulation (WB-EMS) provide a very effective form of resistance training. We hypothesized that WB-EMS reduces VF and improves plasma glucose measures in older non-insulin dependent diabetes mellitus (NIDDM) males and females. Methods: A four-arm age-matched case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…Five randomized and non-randomized trials or intervention studies without CG applied WB-EMS for two to four months in cohorts with non-insulin dependent Diabetes Mellitus (NIDDM) ( 17 , 18 , 35 , 37 , 39 ) 5 . Two of the studies included hospitalized cohorts with end-stage diabetes kidney disease ( 37 ) or diabetic ulcers undergoing minor amputation ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five randomized and non-randomized trials or intervention studies without CG applied WB-EMS for two to four months in cohorts with non-insulin dependent Diabetes Mellitus (NIDDM) ( 17 , 18 , 35 , 37 , 39 ) 5 . Two of the studies included hospitalized cohorts with end-stage diabetes kidney disease ( 37 ) or diabetic ulcers undergoing minor amputation ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…More than two thirds of the studies/projects reported changes body composition parameters as primary, secondary or tertiary outcome. Although difficult to conclude 8 , about 14 studies considered changes in body composition and anthropometry at least as a core outcome [21,23,27,39,44,49,50,53,54,58,59,63,68,77] (Figure 3 31,39,44,57,75,92], one study [37] relied on the caliper method and a further study [53] determined changes in thigh and calf circumference.…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%
“…Apart from total body fat, several studies determined trunk, abdominal, or visceral fat mass/rate by BIA [46,65], DXA [19,31,39,41] or CT [68] or, less sophisticated, by waist circumference [19, 21,39,65,71,75,94]. Eleven studies focus on local muscle parameters (muscle thickness, cross-sectional area, crosssectional volume) predominately at the mid-thigh/quadriceps site [23,27,29,46,54,58,59,63,68,83,86], calf [23] or upper arm [27] applying either ultrasound (US) [23,27,29,63,86], computed tomography (CT) [58,59,68] or magnetic resonance imaging (MRI) [46,83] techniques.…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%
See 2 more Smart Citations